ONLINE ORDERING WEBSITE IN KITCHEN KARANG USING JOOMLA 1.5.15 AND VIRTUEMART 1.1.4 - Novianti Wulandari; Irfan, S. Kom, MMSI Irfan, S. Kom, MMSI (Jurnal Sistem Informasi, 2009)
As one of the current business dining These are commonly found everywhere, so theKitchen Coral more must increase its sales require a Kitchen Coral agar media morewidely known to the public and easy online reservations. For that online bookingwebsite was made to simplify the Coral Kitchen customers. To build this websiteauthors use a version of 1.5.15 and Joomla applications VirtueMart 1.1.4 is based oncontent management system (CMS). Due to this application to apply system thatoriented towards content, making it easier for the users and administrators to be ableto provide contributions into the website without a difficult procedure.